Blue light exposure in the workplace: a case study of nail salons. Issue 5 (28th May 2022) - Lee, SoYoung; Gaskin, Sharyn; Piccoli, Bruno; Pisaniello, Dino
Abstract: Fluorescent or LED nail lamps are used in manicure and pedicure salons to cure nail coatings. These are UV sources, but with significant blue light emissions. Most of the literature emphasizes skin damage and cancer risk from UV exposure rather than blue light-induced damage to visual photoreceptors. Nail technicians using the lamps routinely may have potentially greater exposure than customers. However, there are no data on blue light radiance levels combined with time activity patterns for exposure assessment. This research aimed to determine exposures through simulation experiments, informed by observational studies in seven nail salons. Typical and worst-case time activity patterns were established, and spectral radiance doses determined in the occupational visual field for two LED nail curing lamps. The results showed the effective spectral radiance dose were below the current guideline promulgated by the International Commission on Non-Ionising Radiation Protection. Interestingly, radiances at the corners of one LED nail curing lamp was higher than at the center, which shows the amount of exposure can differ depending on the viewing angle. This research is the first to determine spectral radiance doses. A covered design is highly recommended for blocking the emission of blue light from a nail lamp.